KETERTELUSURAN DALAM RANTAI PASOK MAKANAN BEKU DI CV SAKANA INDO PRIMA - Ardhy Lazuardy; Faldy Yardan Pratama; Khibrankhair Putra Sulviawan; Sekar Chanya Dewani (Jurnal Ilmiah Teknik, 2022)
Developing a traceability system in the frozen food supply chain at CV Sakana Indo Prima. Frozen food in its processing has potential hazards that affect the quality and safety of food along the supply chain of frozen food products. These hazards include microbiological, physical, and chemical hazards that foodstuffs can experience during the production process to the hands of the final consumer. The development of this traceability system is divided into three stages. The first stage, namely by mapping and assessing supply chain performance, is carried out by identifying indicators of each level of SCM performance, calculating normalization values based on the initial value of KPIs using the norm de boer equation or formula, and calculating the final value of supply chain performance. The second stage is to carry out quality assurance by implementing the Hazard Analysis Critical Control Points (HACCP) system. Hazard analysis, hazard category determination, and critical control points and control measures. Determination of hazard categories as well as determination of essential points of control and control measures.